Both quiescent and proliferating cells circulate in the blood of the invasive apple snail Pomacea canaliculata. Issue 107 (December 2020) - Rodriguez, Cristian; Simon, Valeska; Conget, Paulette; Vega, Israel A.
Abstract: Gastropod hematopoiesis occurs at specialized tissues in some species, but the evidence also suggests that hemocyte generation is maybe widespread in the connective tissues or the blood system in others. In Ampullariidae (Caenogastropoda), both the kidney and the lung contain putative hematopoietic cells, which react to immune challenges. In the current study, we wanted to explore if hematopoiesis occurs in the blood of Pomacea canaliculata . Thus, we obtained circulating hemocytes from donor animals and tested their ability to proliferate in the blood of conspecific recipients. We tracked cell proliferation by labeling the donors' hemocytes with the fluorescent cell proliferation marker carboxyfluorescein diacetate succinimidyl ester (CFSE). Transferred CFSE-labeled hemocytes survived and proliferated into the recipients' circulation for at least 17 days. We also determined the cell cycle status of circulating hemocytes by using the propidium iodide (PI) and acridine orange (AO) staining methods. Flow cytometry analyses showed that most PI-stained hemocytes were in the G1 phase (~96%), while a lower proportion of cells were through the G2/S-M transition (~4%). When we instead used AO-staining, we further distinguished a subpopulation of cells (~5%) of low size, complexity-granularity, and RNA content. We regarded this subpopulation as quiescent cells. In separate experimental sets, we complemented these findings by assessing in circulating hemocytes two evolutionary conserved features of quiescent, undifferentiated cells. First, we used JC-1 staining to determine the mitochondrial membrane potential (Ψm ) of circulating hemocytes, which is expected to be low in quiescent cells. Most hemocytes (~87%) showed high aggregation of JC-1, which indicates a high Ψm . Besides that, a small hemocyte subpopulation (~11%) showed low aggregation of the dye, thus indicating a low Ψm . It is known that the transition from a quiescent to a proliferating state associates with an increase of the Ψm . The specificity of these changes was here controlled by membrane depolarization with the Ψm disruptor CCCP. Second, we stained hemocytes with Hoechst33342 dye to determine the efflux activity of ABC transporters, which participate in the multixenobiotic resistance system characteristic of undifferentiated cells. Most hemocytes (>99%) showed a low dye-efflux activity, but a small proportion of cells (0.06–0.12%) showed a high dye-efflux activity, which was significantly inhibited by 100 and 500 μM verapamil, and thus is indicative of an undifferentiated subpopulation of circulating hemocytes. Taken together, our results suggest that, among circulating hemocytes, there are cells with the ability to proliferate or to stay in a quiescent state and behave as progenitor cells later, either in the circulation or the hematopoietic tissues/organs. Highlights: Circulating hemocytes in different cycle stages are first reported in a gastropod. Quiescent hemocytes with low RNA content are found in the circulation (G1q cells). Transferred CFSE-labeled cells divide in the circulation of recipient snails. Hemocytes with stem cell-like features normally circulate in the snails' blood.